Implementation of AJAX and JSON to improve web application performance - Muhammad Zakki Abdillah (Jurnal Transformatika, 2016)
AJAX is not a language programming, but a technic that possible to create interactive web application. With AJAX, web application can interaction with server in back screen, so not influence web page overall. The method of displaying the  result request from user and viewed in to system without must reload page overall. AJAX representation performed with creating programming in the system. This research provides a bridge between the user request and server response, so as to ease the burden of the server as seen from the server memory in unused. The result from this research is system can provides a faster display from the previous system. Testing system based on a rapid access on each menu. The result comparison between the old system and the new system is 43,8 versus 78,4 and server memory used is 2.112 MB versus 2.095 MB with 8 users. This comparison provides information that system with AJAX better to be used on building a system